Double Chambered Right Ventricle with Ventricular Septal Defect in Adults: Case Series and Review of the Literature - Moustafa, Sherif (J Cardiovasc Ultrasound, 2015)
Double-chambered right ventricle (DCRV) is an uncommon congenital anomaly in which anomalous muscle bands divide the right ventricle into two chambers; a proximal high-pressure and distal low-pressure chamber. It may be associated with mid right ventricular obstruction. It is commonly associated with other congenital anomalies, most frequently perimembranous ventricular septal defect (PM-VSD). We herein present 5 adult patients with concomitant DCRV and PM-VSD who varied in their symptomatic presentations and the ways of management.